Association of central blood pressure with an exaggerated blood pressure response to exercise among elite athletes - Most, A.; Kraushaar, L.; Dörr, O.; Keranov, S.; Hoelscher, S.; Weber, R.; Akdogan, E.; Groesser, V.; Husain-Syed, F.; Nef, H.; Hamm, C. W.; Bauer, P. (European Journal of Applied Physiology, 2023)
Purpose The systolic blood pressure/workload (SBP/MET) slope was recently reported to be a reliable parameter to identify an exaggerated blood pressure response (eBPR) in the normal population and in athletes. However, it is unclear whether an eBPR correlates with central blood pressure (CBP) and vascular function in elite athletes.